2014
DOI: 10.1007/s00520-014-2128-0
|View full text |Cite
|
Sign up to set email alerts
|

The use of Instanyl® in the treatment of breakthrough pain in cancer patients: a 3-month observational, prospective, cohort study

Abstract: PurposeInstanyl® (intranasal fentanyl spray) is a novel treatment for breakthrough pain (BTP) in cancer patients. It has shown a rapid onset of pain relief in clinical trials. This study examines the use of Instanyl® in real-life settings.MethodsA 3-month observational, prospective, cohort study of cancer patients with BTP receiving Instanyl® (50, 100, or 200 μg) under routine clinical practice. Data were collected at three time points corresponding with routine clinic visits – baseline, Week 4, and Week 13. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 21 publications
0
7
0
1
Order By: Relevance
“…Relief from acute, unpredictable, and highly distressing pain events, such as breakthrough cancer pain, has been improved with IN formulations of fentanyl (Karlsen et al, 2014;Kongsgaard ABBREVIATIONS: CFN, carfentanil; DVR, distribution volume ratio; IM, intramuscular, intramuscularly; IN, intranasal, intranasally; IV, intravenous, intravenously; MPE, maximum percent effect; NLX, naloxone; PET, positron emission tomography; PK, pharmacokinetics; RO, receptor occupancy; VOI, volumes-of-interest.…”
Section: Introductionmentioning
confidence: 99%
“…Relief from acute, unpredictable, and highly distressing pain events, such as breakthrough cancer pain, has been improved with IN formulations of fentanyl (Karlsen et al, 2014;Kongsgaard ABBREVIATIONS: CFN, carfentanil; DVR, distribution volume ratio; IM, intramuscular, intramuscularly; IN, intranasal, intranasally; IV, intravenous, intravenously; MPE, maximum percent effect; NLX, naloxone; PET, positron emission tomography; PK, pharmacokinetics; RO, receptor occupancy; VOI, volumes-of-interest.…”
Section: Introductionmentioning
confidence: 99%
“…Other than death, discontinuation occurred for lack of efficacy or other reasons. The treatment improved patients' satisfaction and brief pain inventory from baseline to the fourth week [45].…”
Section: Discussionmentioning
confidence: 91%
“…48 In a noninterventional, 3month observational study, Patient Treatment Satisfaction Scale scores reported a mean (SD) 36.8% (57.9%; n = 37; P < .001) increase from baseline to week 4 of intranasal fentanyl treatment. 49 In another study, 77.4% favored intranasal fentanyl compared with 22.6% of patients favoring oral transmucosal fentanyl citrate (P < .001). 47 Regarding ease of use, 90.1% of patients rated easy/very easy to administer intranasal medication compared with 39.8% of patients for oral transmucosal fentanyl citrate.…”
Section: Patient Acceptability and Preferencementioning
confidence: 96%
“…45,[47][48][49]78 Common adverse events are drowsiness, nausea, vomiting, and nasal pruritus. 45,[47][48][49]78 Severe and serious adverse events have been reported, which include dysgeusia, skin pain, and nasal ulcer.…”
Section: Intranasal Fentanyl and Pectin Nasal Spray Formulationsmentioning
confidence: 99%
See 1 more Smart Citation